'Bartlett' pear fruit (Pyrus communis L.) ripening regulation by low temperatures involves genes associated with jasmonic acid, cold response, and transcription factors. (July 2017) - Nham, Ngoc T.; Macnish, Andrew J.; Zakharov, Florence; Mitcham, Elizabeth J.
Highlights: Transcription profiles of pear fruit with enhanced ripening rates, induced by low temperatures, were generated. Jasmonic acid (JA) appears to negatively regulate ripening in pear. JA ripening regulation may act independently or upstream of ethylene pathway. Transcription factors associated with ripening enhancement by low temperatures were determined. Abstract: Low temperature (LT) treatments enhance ethylene production and ripening rate in the European pear ( Pyrus communis L.). However, the underlying molecular mechanisms are not well understood. This study aims to identify genes responsible for ripening enhancement by LT. To this end, the transcriptome of 'Bartlett' pears treated with LT (0 °C or 10 °C for up to 14 d), which results in faster ripening, and control pears without conditioning treatment was analyzed. LT conditioned pears reached eating firmness (18 N) in 6 d while control pears took about 12 d when left to ripen at 20 °C. We identified 8, 536 differentially expressed (DE) genes between the 0 °C-treated and control fruit, and 7, 938 DE genes between the 10 °C-treated and control fruit. In an attempt to differentiate temperature-induced vs. ethylene-responsive pathways, we also monitored gene expression in fruit sequentially treated with 1-MCP then exposed to low temperature. This analysis revealed that genes associated with jasmonic acid biosynthesis and signaling, as well as the transcription factors TCP9a, TCP9b, CBF1, CBF4, AGL24, MYB1R1, and HsfB2b could be involved in the LT-mediated enhancement of ripening independently or upstream of ethylene.